HUBUNGAN TINGKAT KEPATUHAN DAN PENGETAHUAN PASIEN TERHADAP PENGOBATAN TUBERKULOSIS PARU DI PUSKESMAS MEKARMUKTI TAHUN 2025 - Evellia Priastuti; Dewi, Masita Sari; Adiwisastra, Nuzul Gyanata; Marselina, Marselina (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Tuberculosis (TB) is a global and national public health problem, as well as an important indicator of achieving the Sustainable Development Goals (SDGs). Indonesia continues to face a high burden of tuberculosis, ranking second after India with millions of cases each year. Treatment success rates have not yet reached the national target, while West Java, including Bekasi Regency, records the highest cases. At Mekarmukti Health Center, in 2016 there were 81 new smear-positive pulmonary TB cases and 16 old cases, with a total of 97 patients, highlighting the importance of sustainable control at primary health services. This study aims to analyze the relationship between knowledge and treatment adherence among TB patients at Mekarmukti Health Center. This quantitative research employed an observational method with a total sampling technique involving 95 respondents. The instrument used was a questionnaire, and data analysis was conducted using the chi-square test. The results showed a relationship between age and knowledge (p=0.000), education and knowledge (p=0.041), as well as treatment category and knowledge (p=0.028). Age was also associated with adherence (p=0.002). However, knowledge was not significantly associated with adherence (p=0.337).